Invitro Anti-mycotic Activity of Hydro Alcoholic Extracts of Some Indian Medicinal Plants against Fluconazole Resistant Candida albicans - Saranya Varadarajan; Malathi Narasimhan; Malaiyandi Malaisamy; Chamundeeswari Duraipandian (Journal of Clinical and Diagnostic Research, 2015)
Background: Candidiasis is one of the most common opportunistic infections caused by Candida albicans. Fluconazole is the drug of choice for prevention and management of this condition. However, the emergence of fluconazole resistant candidal strains has become a major concern. Many herbs like fenugreek, cinnamon, papaya, oregano, garlic are rich in phytochemical constituents known to express antimycotic activity. With the available information, the present research study was carried out to assess the invitro antimycotic activity of hydro alcoholic extracts of Trigonella foenumgraecum seeds, Cinnamomum verum bark and Carica papaya leaves and seeds against fluconazole resistant Candida albicans Materials and Methods: Hydro alcoholic extracts of Trigonella foenum-graecum (seeds), Cinnamomum verum (bark), Carica papaya CO.2 strain (male and female leaves) and Carica papaya CO.2 strain (seeds) were prepared by maceration. The anti-mycotic activity of the prepared extracts against Candida albicans was assessed by agar well diffusion method. Three independent experiments were performed in triplicates and the mean and standard deviation were calculated. Minimum inhibitory concentration was determined. Results: The results of the present study revealed that all the extracts exhibited anti-mycotic activity in a dose dependent manner and minimum inhibitory concentration of all the extracts was found to be 15.62 µg/ml. Conclusion: The results of the present study shed light on the fact that plant extracts could be used not only as an alternate drug for management of fluconazole resistant candidiasis but also explored further for oral cancer prevention as a therapeutic adjunct.